Intellectual Virtue in Critical Thinking and Its Instruction: Introduction to a Symposium - Ferkany, Matt; McKeon, Matt; Godden, David (Informal Logic, 2023)
How is intellectual virtue related to critical thinking? Can one be a critical thinker without exercising intellectual virtue? Can one be intellectually virtuous without thereby being a critical thinker?  How should our answers to these questions inform the instruction of critical thinking? These were the questions informing the 2023 Charles McCracken endowed lectureships given at Michigan State University by Professors Harvey Siegel and Jason Baehr. This brief commentary introduces their respective papers, which appear in the current issue of Informal Logic.